An evaluation of synergistic interactions between feruloyl esterases and xylanases during the hydrolysis of various pre-treated agricultural residues - Mkabayi, Lithalethu (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology)
Agricultural residues are readily available and inexpensive renewable resources that can be used as raw materials for the production of value-added chemicals. The application of enzymes to facilitate the degradation of agricultural residues has long been considered the most environmentally friendly strategy for converting this material into good quality value-added chemicals. However, agricultural residues are typically lignocellulosic in composition and recalcitrant to enzymatic hydrolysis. Due to this recalcitrant nature, the complete degradation of biomass residues requires the synergistic action of a broad range of enzymes. The development and optimisation of synergistic enzyme cocktails is an effective approach for achieving high hydrolysis efficiency of lignocellulosic biomass. The aim of the current study was to evaluate the synergistic interactions between two termite metagenome-derived feruloyl esterases (FAE6 and FAE5) and endo-xylanases for the production of hydroxycinnamic acids and xylo-oligosaccharides (XOS) from model substrates, and untreated and pre-treated agricultural residues. Firstly, the two fae genes were heterologously expressed in Escherichia coli, and the recombinant enzymes were purified to homogeneity. The biochemical properties of the purified recombinant FAEs and xylanases (XT6 and Xyn11) were then assessed to determine the factors which influenced their activities and to select suitable operating conditions for synergy studies. An optimal protein loading ratio of xylanases to FAEs required to maximise the release of both reducing sugar and ferulic acid (FA) was established using 0.5% (w/v) insoluble wheat arabinoxylan (a model substrate). The enzyme combination of 66% xylanase and 33% FAE (on a protein loading basis) produced the highest amounts of reducing sugars and FA. The enzyme combination of XT6 (GH10 xylanase) and FAE5 or FAE6 liberated the highest amount of FA while a combination of Xyn11 (GH11 xylanase) and FAE5 or FAE6 produced the highest reducing sugar content. The synergistic interactions which were established between the xylanases and FAEs were further investigated using agricultural residues (corn cobs, rice straw and sugarcane bagasse). The three substrates were subjected to hydrothermal and dilute acid pre-treatment prior to synergy studies. It is generally known that, during pre-treatment, many compounds can be produced which may influence enzymatic hydrolysis. The effects of these by-products were assessed and it was found that lignin and its degradation products were the most inhibitory to the FAEs. The optimised enzyme cocktail was then applied to 1% (w/v) of untreated and pre-treated substrates for the efficient production of XOS and hydroxycinnamic acids. A significant improvement in xylanase substrate degradation was observed, especially with the combination of 66% Xyn11 and 33% FAE6 which displayed an improvement in reducing sugars of approximately 1.9-fold and 3.4-fold for hydrothermal and acid pre-treated corn cobs (compared to when Xyn11 was used alone), respectively. The study demonstrated that pre-treatment substantially enhanced the enzymatic hydrolysis of corn cobs and rice straw. Analysis of the hydrolysate product profiles revealed that the optimised enzyme cocktail displayed great potential for releasing XOS with a low degree of polymerisation. In conclusion, this study provided significant insights into the mechanism of synergistic interactions between xylanases and metagenome-derived FAEs during the hydrolysis of various substrates. The study also demonstrated that optimised enzyme cocktails combined with low severity pre-treatment can facilitate the potential use of xylan-rich lignocellulosic biomass for the production of valuable products in the future.
Keywords: Esterases; Xylanases; Hydrolysis; Agricultural wastes -- Recycling; Enzymes; Lignocellulose -- Biodegradation; Escherichia coli; Oligosaccharides; Hydroxycinnamic acids